Students’ sexual exposure in tertiary institutions: a case study of some universities in Abia state of Nigeria - Enwereji, E. E.; Akubugwo, E. I.; Onwuka, J. O.; Ckikezie, D. C. (International Journal Of Community Medicine And Public Health, 2017)
Background: Studies have shown that new entrants in institutions of higher learning are at risk of sexual exploits by older students. Drama has been identified as an intervention strategy capable of internalizing both the emotional and cognitive dimensions of sexual problems for positive changes. This study used drama to create awareness on likely common sexual exploits in institutions of higher learning. Methods: Study used first year students in three universities, federal, state and private. It was assumed that first year students in institutions of higher learning are likely to be exposed to sexual overtures by older students. It was considered that using drama as an intervention will create awareness on types of sexual overtures experienced in tertiary institutions. A random sample of ninety ((90) students, comprising thirty (30) students in each of the universities studied was selected. Pre- and post-self-administered questionnaire were given to the selected students to complete. On completion, copies of the questionnaire (pre- and post) were analyzed using Tables and percentages. Results: The study showed that students in the three universities studied were approached for sex by fellow students but this was more in Rhema University 8 (28. 8%) than in other universities. Both male and female sexes approached the students for sex. Finding showed that some students practiced anal, oral, and multiple sex, but this was more in MOUA 10 (33.3%) than in ABSU and Rhema with 9 (30%) respectively. For knowledge on how HIV is transmitted, students had the knowledge that HIV transmission occurs by sharing sharp objects. This knowledge was more among students in MOUA 29 (97%) than those in ABSU 28 (93%) and Rhema 27 (90%). Conclusions: Drama therefore, is a valuable and timely intervention strategy capable of encouraging HIV risk reduction among university students.